Production performance of white shrimp Litopenaeus vannamei with super-intensive culture on different rearing densities - Andhika Rakhmanda; Agung Pribadi; Parjiyo Parjiyo; Bobby Indra Gunawan Wibisono (Jurnal Akuakultur Indonesia)
This research aimed to evaluate the production performance of white shrimp Litopenaeus vannamei with super-intensive culture on different rearing densities. The research was conducted at PT. Dewi Laut Aquaculture, Cikelet, Garut, West Java. As many of 8 ponds were used and divided into 2 groups based on the stock density of shrimp, 550 ind/m2 and 650 ind/m2, and reared for 99 days. The results showed that super-intensive shrimp culture at the density of 550–650 ind/m2 potentially produced shrimp with average body weight ranged from 15.91–19.31 g, survival rate 62.67–87.95%, growth 0.16 to 0.20 g/day, FCR 1.35–1.66, and productivity reach 5.55–9.19 kg/m2. There were no significant differences between the two stocking densities in body weight, growth, and feed conversion performance, while ponds with higher rearing density had better survival and productivity than ponds with lower rearing density. L. vannamei cultured at a density of 650 ind/m2 produces the best performance and most feasible to be applied in super-intensive white shrimp cultivation.